2016
DOI: 10.1016/j.jneuroim.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

T cell cytokine signatures: Biomarkers in pediatric multiple sclerosis

Abstract: Although Multiple Sclerosis is predominantly regarded as a disease of young adulthood, up to five percent of MS patients are diagnosed prior to age eighteen. The predominant form of MS is relapsing-remitting characterized by exacerbations of symptoms followed by periods of remission. The majority of disease modifying drugs target T cell proliferation or block migration into the central nervous system. Although these treatments reduce relapses, disease progression still occurs, warranting therapeutic strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…There are recent reports that more of these cytokines are elevated relative to healthy controls in pediatric RRMS patients with diagnosed relapse compared to patients in remission. 96 …”
Section: Discussionmentioning
confidence: 99%
“…There are recent reports that more of these cytokines are elevated relative to healthy controls in pediatric RRMS patients with diagnosed relapse compared to patients in remission. 96 …”
Section: Discussionmentioning
confidence: 99%
“…Cytokines regulate immune cell infiltration into different areas of the CNS, resulting in different clinical manifestations in animal models of MS (Cala et al 2016). Both IFN-c-secreting T H 1 cells and IL-17-secreting T H 17 cells are associated with activation of encephalitogenic T-cells, CNS inflammation, and demyelinating lesions (Wang et al 2006;Fletcher et al 2010;Lovett-Racke et al 2011;Rostami & Ciric 2013).…”
Section: Discussionmentioning
confidence: 99%
“…60 Finally, one study showed that the serum T-cell cytokine signatures from pediatric MS patients differed from healthy controls, with certain serum cytokines (IL-10, IL-21, IL-23, and IL-27) predicting MS relapse. 61 B-cell immunology plays an important role in mediating inflammatory CNS disease. Circulating serum antibodies against myelin basic protein were not elevated in children with MS compared with controls in one study.…”
Section: Immunology Of Multiple Sclerosis In Childrenmentioning
confidence: 99%